Wavering or privileged cooperation?: Portugal and Lusophone Africa at the UN General Assembly - Seabra, P.; Mesquita, R. (Portugal and the Lusophone world: Law, geopolitics and institutional cooperation, 2023)
Relations between former colonial powers and former colonies are often characterized by ambivalent political outcomes and mismatched rhetoric. Portugal’s interactions with its own former African colonies since 1975 are not an exception and have been routinely depicted by similar oscillating dynamics. They remain, nevertheless, grounded by the expectation of privileged contacts and mutual alignment in several different international fora. This chapter evaluates claims of pre-established international affinity as a proxy product of a shared decolonization legacy and highlights key intricacies of Lusophone political cooperation in the international domain. We explore whether the creation of the Community of Portuguese Speaking Countries (CPLP) has indeed fostered closer ties between this set of countries in key multilateral platforms by quantitively analysing sponsorship patterns at the United Nations General Assembly (UNGA) in the last two decades. Our results demystify broader claims of privileged relations, yet still point to considerable room for manoeuvre in institutionally dense formats such as the UN.